2013
DOI: 10.1016/j.ramb.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety symptoms in crack cocaine and inhalant users admitted to a psychiatric hospital in southern Brazil

Abstract: A significant difference regarding anxiety symptomatology, especially state anxiety, was observed among inhalant and crack users. Anxiety and overall mental psychopathology were significantly correlated in this sample. The results indicate that screening initiatives to detect anxiety and additional psychiatric comorbidities among crack and inhalant users are feasible and relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 68 publications
2
15
1
1
Order By: Relevance
“…The open-field test is considered a test to evaluate anxiety (Sudakov et al, 2013), but there are several more specific tests, such as the elevated plus maze test (Pellow, Chopin, File, & Briley, 1985). The decrease in the anxiety levels in the present study disagrees with human reports of crack exposure, in which increased anxiety is sometimes reported (Delas et al, 2010;Lejuez et al, 2008;Zubaran, Foresti, Thorell, & Franceschini, 2013). Therefore, future studies will use our exposure model and observe exposed rats in other anxiety tests, such as the elevated plus maze, to support the present results.…”
Section: Discussioncontrasting
confidence: 76%
“…The open-field test is considered a test to evaluate anxiety (Sudakov et al, 2013), but there are several more specific tests, such as the elevated plus maze test (Pellow, Chopin, File, & Briley, 1985). The decrease in the anxiety levels in the present study disagrees with human reports of crack exposure, in which increased anxiety is sometimes reported (Delas et al, 2010;Lejuez et al, 2008;Zubaran, Foresti, Thorell, & Franceschini, 2013). Therefore, future studies will use our exposure model and observe exposed rats in other anxiety tests, such as the elevated plus maze, to support the present results.…”
Section: Discussioncontrasting
confidence: 76%
“…Although in this study, we have not assessed whether emotional regulation occurs during chronic cocaine administration, the fact that the OTR dysregulation in the LS and amygdala occurred both following cocaine administration and withdrawal suggests that behavioural deficits would have been also present during chronic cocaine exposure. Indeed, earlier studies have identified emotional deficits during chronic cocaine exposure in both animals (Morales‐Rivera et al ., ) and humans (Morton, ; Zubaran et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Among the psychostimulant drugs, cocaine use disorder (CUD) is associated with greater physiological alterations, given that it acts blocking dopamine, serotonin and norepinephrine reuptake (2, 3). Furthermore, cocaine triggers cellular toxicity through different mechanisms, including immune dysregulation (4, 5) and oxidative damage (6, 7), potentially leading to neurological, emotional, and cognitive impairments (8, 9). Studies also observed higher risk of contracting or transmitting infectious diseases among cocaine users compared to non-users (1012).…”
Section: Introductionmentioning
confidence: 99%